A theoretical extension and empirical investigation for continuance use in social networking sites - Shanmugam, Mohana; Jusoh, Yusmadi Yah; Nor, Rozi Nor Haizan; A. Jabar, Marzanah (Asian Research Publishing Network, 2015)
Social commerce is a relatively new stream mediated by the proliferation of Social Networking Sites (SNSs) and the popularity of social media. The social commerce wave has opened up vast opportunities in emerging markets through online communities’ participation. Knowledge sharing and learning through online communities are made possible with the active collaboration and interaction among groups of individuals. This study investigates on the role of social media in facilitating online communication of consumers through related theories and constructs, leading to online social support. A conceptual model integrating constructs of the Theory of Planned Behavior (TPB), Social Support Theory (SST), perceived value and satisfaction is developed to augment our understanding on the continuance participation from the intention and behavioral perspectives. The study therefore introduces a continuance participation model that integrates the emotional and informational constructs from the SST, TPB, perceived value and satisfaction in SNSs to establish a theoretical foundation for the study of continuance participation in online communities. A survey conducted on users of SNSs with a total of 285 final respondents empirically tests the continuance model constructs with ten hypotheses using Structural Equation Modelling (SEM) approach and Partial Least Square (PLS) methods to which all nine theorized hypotheses are achieved. The results indicate that social interaction through social support has an intense influence on perceived value and satisfaction resulting in an increased continuance participation intention and behavior in online communities. Additionally, the model reveals that the constructs perceived behavioural control, subjective norms, and attitude from the Theory of Planned Behaviour alongside with Social Support constructs, satisfaction and a perceived value construct significantly influence online communities’ continuance participation intention and behaviour. This paper also seeks to enlighten our knowledge on online communities and tap into the social commerce capabilities particularly looking into continuance participation from the intention and behavioral perspectives. The findings of this study contributes to the social commerce school of thought by theoretically developing research in online communities by proposing social constructs from a social psychology theory in increasing our understanding on continuance model. The theoretical base of this study is the primary contribution of this research. In addition, it complements the minority theoretical background that surfaces in the area of social commerce distinctly looking at online communities.